1997
DOI: 10.1180/claymin.1997.032.4.09
|View full text |Cite
|
Sign up to set email alerts
|

The structure of an intercalated ordered kaolinite — a Raman microscopy study

Abstract: A B S T R A C T: Changes in the molecular structure of a highly ordered kaolinite, intercalated with urea and potassium acetate, have been studied using Raman microscopy. A new Raman band, attributed to the inner surface hydroxyl groups strongly hydrogen bound to the acetate, is observed at 3605 cm -1 for the potassium acetate intercalate with the consequential loss of intensity in the bands at 3652, 3670, 3684 and 3693 cm -l. Remarkable changes in intensity of the Raman spectral bands of the low-frequency reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 15 publications
5
85
2
1
Order By: Relevance
“…Raman spectra of urea-intercalated kaolinite at room temperature have been reported recently [3][4][5]. The present paper reports the Raman spectra of urea-intercalated kaolinite (ordered and disordered) at 77K.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Raman spectra of urea-intercalated kaolinite at room temperature have been reported recently [3][4][5]. The present paper reports the Raman spectra of urea-intercalated kaolinite (ordered and disordered) at 77K.…”
Section: Introductionmentioning
confidence: 94%
“…In recent Raman studies at room temperature [4,5], evidence was found for hydrogen bonding involving the NH 2 groups, rather than the C=O group of urea. Large shifts in the NH stretching bands of urea were observed, but there was little change in the intensity of the bands attributed to vibrations of the inner surface hydroxyl groups.…”
Section: Urea-intercalated Kaolinitementioning
confidence: 99%
“…Depending on pH, different cationic species may be held to the clay surface at appropriate ion-exchange sites. 27 …”
Section: Kinetic Processesmentioning
confidence: 99%
“…The adsorption using the Lagergren model can also be explored, [26][27][28][29][30][31][32][33][34][35][36][37][38] as proposed in equation 12.…”
Section: Kinetic Processesmentioning
confidence: 99%
See 1 more Smart Citation